Caracterización del sistema de Tenecia, Perfil Hematologico-Bioquimico del Cerdo Criollo Ecuatoriano en la Provincia de Tungurahua. - Ayala Camalle, Luis Xavier (2018)
Thsi research was carried out in the province of Tungurahua, its aim is to characterize of the tenure system and stablish the haematological - biochemical profile of the Ecuadorian Creole pig. It was developed through surveys to 100 people, it sought overall information, technological data, flocks structure, productive date, breeding data, nourish data, infrastructure and economy. The study of haematological - biochemical profile was developed in 30 pigs, blood samples were collected from the atrial vein in each pig, those one were located in 9 cantons of Tungurahua (Ambato, Cevallos, Pillaro, Patate, Pelileo, Quero, Mocha, Tisaleo y Baños), those samples were analyzed at the "San Francisco" Clinical Laboratory located in Ambato. After that, getting the results it is able to compare the statistics values of the following variables; haematological profile (hematocrit, hemoglobin, erythrocytes, VGM, HCM, CGMH, platelets, leukocytes, neutrophils, n. bands, lymphocytes, monocytes, eosinophils, basophils), chemical profile (glucose, urea, BUN, creatinine, AST, ALT, total proteins, calcium, phosphorus, potassium). In the comparison of the analyzes it was observed that in the tenure system the data obtained shows negative results in management and care of the pigs due to its lack of trading and its long period of breeding development. While haematological - biochemical profile, their variables are altered according to the type of feeding provided in each sector investigated. In the results of the haematological profile with relation to sex between male and female, most of their values did not have a significant difference, only in the case of lymphocytes there was a significant difference in (8834,05 ± 659,54a for males and 6367,60 ± 932,73b for females) it was caused by the nourishment, , exercise, as well as the effect of stress.